Challenges and opportunities of social work Internship in Kurdistan Reagin of Iraq - Qadir, Prof.Dr.Zhiya Abbas Qadir; Karim, Ass Prof .Dr.Luqman Saleh Karim; Miran, Dunya Salahadin Miran (Sulaimani Journal for Humanities, 2026)
The establishment of both social work departments is recent in KRI, in Salahaddin University it was established in 2008, while at Sulaimani University it was founded in 2014. As an essential part of the social work curriculum, the internship program is designed to meet social workers capability on the ground. Accordingly, in both departments one-day internship program at third and fourth stages is designed to practice at; schools, government entities, local and international organizations. However, along with the available opportunities, many challenges are facing the process of the internship. On the one hand, lack of internship guideline, and lack of job description for social worker who enter the field profession in KRI, have made the process facing lots of difficulties. On the other hand, organizations and government settings have limitations for those social workers who apply to practice in their institutions if they are accepted to attend the settings and do there their field work. This research aims to identify the most important internship opportunities and challenges that students of social work face in KRI on different levels. To reach the aims, the researchers used scientific qualitative methods by conducting semi-structured interviews and focus group discussions (FGD) in both departments with students of social work, teachers, supervisors, organization, and social workers at government entities. Moreover, the final part of the research provides recommendations and suggestions to fill the gap in the process and provide a qualified atmosphere for social work internship performance in KRI.
Keywords: Internship; challenges; opportunities; social work